Diterpene Biosynthesis in Rice Blast Fungus Magnaporthe - Shahi, Ayousha; Yu, Houlin; Mafu, Sibongile (Frontiers in Fungal Biology, 2022)
Plant-pathogenic fungi harbor various specialized metabolites including diterpenoids that function as hormones and virulence factors. The fungus Magnaporthe oryzae is the causal agent of rice blast disease and can infect over fifty grass species. We demonstrate that rice blast fungi encode two diterpene synthases that produce normal pimara-8,15-diene and manoyl oxide scaffolds. Phylogenetic analysis of diterpene synthases among rice blast pathotypes showed functional conservation of these two core diterpene synthases amongst all pathotypes and suggests further expansion in those infecting select grass species. These insights into the blast fungal terpenome may inform efforts to counteract deleterious phytopathogens in crucial food crops.